Strategic Human Resource Management : An International Perspective - Paul Smith (SAGE Publications, Ltd. (UK), 2021)
Whether you are studying at undergraduate or postgraduate level, our stellar team of expert authors will guide you through the key topics of human resource management from strategic and international perspectives. Starting with the fundamentals of each topic and progressing through to critical evaluation, the 3rd edition includes: Even more international case studies from across Europe, Asia, Australia and the Middle East – which bring the theory and academic underpinning to life A wide range of Reflective Activities that encourage you to consider the real-world implications of what you have learnt An updated companion website featuring a wealth of resources for lecturers and students, including an Instructor’s Manual, PowerPoint slides, a Testbank, recommended journal articles and additional business cases